2001
DOI: 10.1207/s15327914nc391_19
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Acts on the Tumor Cell Invasion Process and Regulates Protease Production

Abstract: Apigenin is a widely distributed plant flavonoid and was proposed as an antitumor agent. In this study, we investigated the apigenin effects on the protease-mediated invasiveness in an estrogen-insensitive breast tumor cell line MDA-MB231. The results show that apigenin at 22.8-45.5 microM (2.5-10 micrograms/ml) strongly inhibited, in a dose-dependent manner, tumor cell invasion through Matrigel, cell migration, and cell proliferation. We show that apigenin treatment from 22.8 microM (2.5 micrograms/ml) led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 36 publications
5
55
0
Order By: Relevance
“…Our results show that apigenin, even though no effect on the expression level and basal secretion of MMP-9, totally abolished the response to PMA stimulation in those cancer cells. Our results are in agreement with the observations that apigenin blocked PMAinduced up-regulation of MMP-9 secretion in MDA-231 breast cancer cells (25). However, they reported that apigenin treatment caused a remarkable decrease at the mRNA and protein levels of urokinase plasminogen activator (u-PA), we failed to detect significant changes in u-PA mRNA expression level in Caski, MDA-231, and SK-Hep1 cell lines (data not shown).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show that apigenin, even though no effect on the expression level and basal secretion of MMP-9, totally abolished the response to PMA stimulation in those cancer cells. Our results are in agreement with the observations that apigenin blocked PMAinduced up-regulation of MMP-9 secretion in MDA-231 breast cancer cells (25). However, they reported that apigenin treatment caused a remarkable decrease at the mRNA and protein levels of urokinase plasminogen activator (u-PA), we failed to detect significant changes in u-PA mRNA expression level in Caski, MDA-231, and SK-Hep1 cell lines (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have identified signal transduction pathways such as ERK and p38 MAPK signaling pathways which were involved in regulation of MMP-2 and MMP-9 expression in malignant cells (25)(26)(27)(28). In our system, PMAinduced MMP-9 expression was strongly attenuated by ERK inhibitor PD98059 or p38 inhibitor SB203580 treatment in Caski cells.…”
Section: Discussionmentioning
confidence: 81%
“…Apigenin has shown promise in inhibiting tumor cell invasion and metastases by regulating protease production (57). Apigenin under in vivo conditions is also effective in inhibiting TNF·-induced intracellular adhesion molecule-1 up-regulation in cultured human endothelial cells (58).…”
Section: Achillea Millefoliummentioning
confidence: 99%
“…Lindenmeyer et al (57) demonstrated the effect of apigenin on protease-mediated invasiveness in estrogen-insensitive breast tumor cell line MDA-MB231, showing that apigenin strongly inhibited tumor cell invasion in a dose-dependent manner. Apigenin inhibits growth and induces G2/M arrest by modulating cyclin-CDK regulators and ERK MAP kinase activation in breast carcinoma cells (80).…”
Section: Apigenin and Cancermentioning
confidence: 99%
“…Studies of human malignant cancer cell lines have shown that apigenin inhibits cancer cell growth via the promotion of cell cycle arrest and apoptosis (8,9). As a candidate anticancer agent, apigenin is of particular interest because it exhibits selective induction of cell cycle arrest and apoptosis in human prostate carcinoma cells without affecting normal cells (10,11).…”
Section: Introductionmentioning
confidence: 99%